The Monotonicity Puzzle: An Experimental Investigation of Incentive Structures - Jeannette Brosig; Christian Lukas; Thomas Riechmann (BuR - Business Research, 2010)
Non-monotone incentive structures, which - according to theory - are able to induce optimal behavior, are often regarded as empirically less relevant for labor relationships. We compare the performance of a theoretically optimal non-monotone contract with a monotone one under controlled laboratory conditions. Implementing some features relevant to real-world employment relationships, our paper demonstrates that, in fact, the frequency of income-maximizing decisions made by agents is higher under the monotone contract. Although this observed behavior does not change the superiority of the non-monotone contract for principals, they do not choose this contract type in a significant way. This is what we call the monotonicity puzzle. Detailed investigations of decisions provide a clue for solving the puzzle and a possible explanation for the popularity of monotone contracts.
urn:nbn:de:0009-20-24985
Keywords: 650; experimental agency; non-monotone contracts; Arbeitsvertrag; Prinzipal-Agent-Theorie; Test; Operations Research